High incidence of hospitalisation due to infectious gastroenteritis in older people associated with poor self-rated health. Issue 12 (30th December 2015) - Chen, Yingxi; Liu, Bette C; Glass, Kathryn; Kirk, Martyn D
Abstract : Objectives: To estimate the incidence and risk factors for gastroenteritis-related hospitalisations in older adults. Design: Longitudinal cohort study. Participants: The 45 and Up Study is a large-scale Australian prospective study of adults aged ≥45 years (mean 62.7 years) at recruitment in 2006–2009. Self-reported demographic, health and dietary information at recruitment from 265 440 participants were linked to infectious gastroenteritis hospitalisation data. Outcome measures: We estimated the incidence of hospitalisation for infectious gastroenteritis, and calculated HRs using Cox regression, adjusting for sociodemographic, health and behavioural variables, with age as the underlying time variable. Results: There were 6077 incident infectious gastroenteritis admissions over 1 111 000 person-years. Incidence increased exponentially with increasing age; from 2.4 per 1000 (95% CI 2.2 to 2.5) in individuals aged 45–54 years to 9.5 per 1000 (95% CI 9.2 to 9.8) in those aged 65+ years. After adjustment, hospitalisation due to infectious gastroenteritis was significantly more common in those reporting use of proton pump inhibitors (HR 1.6, 95% CI 1.5 to 1.7), and those with poorer self-rated health (HR 4.2, 95% CI 3.6 to 4.9). Conclusions: Infectious gastroenteritis results in hospitalisation of approximately 1% of people ≥65 years old each year. Early recognition and supportive treatment of diarrhoea in older patients with poorer self-rated health may prevent subsequent hospitalisation.